UPAYA PENINGKATAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN MENERAPKAN METODE JIGSAW LEARNING PADA SISWA KELAS V SD NEGERI 0701 ROTAN SOGO - Roslina Nasution (Universitas Muhammadiyah Tapanuli Selatan, 2017)
This study is an effort to increase learning achievement by applying the jigsaw learning method on Elementary School fifth grade students of Rattan Sogo 0701. By applying the jigsaw learning method is expected to improve the quality of teaching so that an increase learning achievement. Design of this research is the subject of action by the Elementary School fifth grade students of Rattan Sogo 0701. Collecting data in this study done by observation and written tests individuals and groups at the end of the lesson. Data obtained from each cycle were analyzed with descriptive qualitative and quantitative. The results showed that increased student involvement which have an impact on student achievement has increased after a study carried out by applying jigsaw learning method, with the following results: in the first cycle the average value of 6.21 grade increased to 6.72 in the second cycle and more increased again in the third cycle becomes 8.24